A Systematic, Integrated Study on the Neuroprotective Effects of Hydroxysafflor Yellow A Revealed by H1 NMR-Based Metabonomics and the NF-κB Pathway. (22nd April 2013) - Liu, Yuanyan; Lian, Zeqin; Zhu, Haibo; Wang, Yinghong; Yu, Shishan; Chen, Tingting; Qu, Jing; Li, Jianbei; Ma, Shuanggang; Chen, Xianhong
Abstract : Hydroxysafflor yellow A (HSYA) is the main active component of the Chinese herb Carthamus tinctorius L.. Purified HSYA is used as a neuroprotective agent to prevent cerebral ischemia. Injectable safflor yellow (50 mg, containing 35 mg HSYA) is widely used to treat patients with ischemic cardiocerebrovascular disease. However, it is unknown how HSYA exerts a protective effect on cerebral ischemia at the molecular level. A systematical integrated study, including histopathological examination, neurological evaluation, blood-brain barrier (BBB), metabonomics, and the nuclear factor-κ B (NF-κ B) pathway, was applied to elucidate the pathophysiological mechanisms of HSYA neuroprotection at the molecular level. HSYA could travel across the BBB, significantly reducing the infarct volume and improving the neurological functions of rats with ischemia. Treatment with HSYA could lead to relative corrections of the impaired metabolic pathways through energy metabolism disruption, excitatory amino acid toxicity, oxidative stress, and membrane disruption revealed by 1 H NMR-based metabonomics. Meanwhile, HSYA treatment inhibits the NF-κ B pathway via suppressing proinflammatory cytokine expression and p65 translocation and binding activity while upregulating an anti-inflammatory cytokine.